Integrated transcriptomic and metabolomic analysis reveals the response of pearl oyster (Pinctada fucata martensii) to long-term hypoxia - Yang, Chuangye; Wu, Hailing; Chen, Jiayi; Liao, Yongshan; Mkuye, Robert; Deng, Yuewen; Du, Xiaodong (Marine environmental research, 2023)
The frequency at which organisms are exposed to hypoxic conditions in aquatic environments is increasing due to coastal eutrophication and global warming. To reveal the effects of long-term hypoxic stress on metabolic changes of pearl oyster, commonly known as Pinctada (Pinctada fucata martensii), the present study performed the integrated analysis of transcriptomics and metabolomics to investigate the global changes of genes and metabolites following 25 days hypoxia challenge. Transcriptome analysis detected 1108 differentially expressed genes (DEGs) between the control group and the hypoxia group. The gene ontology (GO) analysis of DEGs revealed that they are significantly enriched in functions such as “microtubule−based process”, “histone (H3–K4, H3–K27, and H4–K20) trimethylation”, “histone H4 acetylation”, “kinesin complex”, and “ATPase activity”, and KEGG pathway functions, such as “DNA replication”, “Apoptosis”, and “MAPK signaling pathways”. Metabolome analysis identified 68 significantly different metabolites from all identified metabolites, and associated with 25 metabolic pathways between the control and hypoxia groups. These pathways included aminoacyl−tRNA biosynthesis, arginine and proline metabolism, and phenylalanine metabolism. Our integrated analysis suggested that pearl oysters were subject to oxidative stress, apoptosis, immune inhibition, and neuronal excitability reduction under long-term hypoxic conditions. We also found a remarkable depression in a variety of biological functions under long-term hypoxia, including metabolic rates, biomineralization activities, and the repression of reorganization of the cytoskeleton and cell metabolism. These findings provide a basis for elucidating the mechanisms used by marine bivalves to cope with long-term hypoxic stress. •Pearl oysters were subject to oxidative stress, apoptosis, and immune inhibition under long-term hypoxic conditions.•Pearl oysters altered their neuronal activity under long-term hypoxic conditions.•Pearl oysters depressed biomineralization process under long-term hypoxia.•Pearl oysters declined the repression of reorganization of the cytoskeleton under long-term hypoxia.